Wybory do Sejmu w 1952 roku w województwie gdańskim w ocenie lokalnych władz partyjnych – próba analizy - Czerwiński, Daniel (Komunizm: System - Ludzie - Dokumentacja, 2014)
The main idea of the article was to show how the 1952 election, were discussed among the members of the Provincial Committee of the Polish United Workers' Party in Gdansk. It was the second voting after the war, but it took place in a completely different reality. In Poland, already in force the new constitution, the society was pacified, and the authorities had no real enemies, but in spite of all in the preparations were included the whole state apparatus. Control over the conduct of the voting was necessary, because the authorities were afraid of a boycott of the election, which was the only form of show opposition to the situation in the People's Republic of Poland. In the post-election analysis, it was emphasized that not everything went as it should, but the Communists and so won. In that Poland, couldn’t have been a different result.